Material characterization of follower assembly of G5 155mm gun Howitzer breach mechanism block - Amran M. Nayan; M.R. Idris; S.R.S. Bakar; M.Y. Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Medium alloy steel is widely used as a material for guns and rocket launchers due to its high strength and excellent machinability characteristics. The purpose of this study is to determine the material properties of the follower assembly used in a breech block gun launcher which is significantly important f or the future product improvement. The microstructure and the effect of alloying elements in the follower assembly is evaluated in this study. The SPECTRO Optical Emission Spectroscopy (ES) method is used to analyse the chemical composition of the material and the Field Emission Scanning Electron Microscope coupled with Energy Dispersive X-Ray (FESEM-EDX) were used to analyse the inclusions of the sample. Results of the ES chemical composition analysis found that Nickel (Ni) is the major alloying elements beside Molybdenum (Mo), Chromium (Cr), Manganese (Mn), Silicon (Si), Sulphur (S), and Carbon (C) while chemical mapping and line scanning analysis of FESEM-EDX on inclusions distributed in the material microstructure identified as a compound of Manganese Sulphur(MnS). Fine dendritic microstructure arrangement and distribution in the microstructure analysis showed that the sample had been quenching in the heat treatment process, which also played a significant role in the material characterization. From the analysis, it is found that the material can be defined as medium alloy steel that is also typical for high strength material for ballistic application.